2017
DOI: 10.1080/1351847x.2017.1282882
|View full text |Cite
|
Sign up to set email alerts
|

On perceptions of financial volatility in price sequences

Abstract: Stock prices in financial markets rise and fall, sometimes dramatically, thus asset returns exhibit volatility. In finance theory, volatility is synonymous with risk and as such represents the dispersion of asset returns about their central tendency (i.e. mean), measured by the standard deviation of returns. When individuals make investment decisions, influenced by perceptions of risk and volatility, they commonly do so by examining graphs of historic price sequences rather than returns. It is unclear, therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 49 publications
7
23
0
Order By: Relevance
“…Using other presentation formats than price paths, prior studies have shown that individuals often do not perceive the overall volatility as risk, but rather shortfall measures such as the probability of incurring a loss (Unser, 2000;Zeisberger, 2018;Holzmeister et al, 2019). Our findings support prior studies which identify that the standard deviation of returns is not the primary factor influencing investor risk perception in price path settings (Duxbury & Summers, 2018;Grosshans & Zeisberger, 2018;Nolte & Schneider, 2018).…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Using other presentation formats than price paths, prior studies have shown that individuals often do not perceive the overall volatility as risk, but rather shortfall measures such as the probability of incurring a loss (Unser, 2000;Zeisberger, 2018;Holzmeister et al, 2019). Our findings support prior studies which identify that the standard deviation of returns is not the primary factor influencing investor risk perception in price path settings (Duxbury & Summers, 2018;Grosshans & Zeisberger, 2018;Nolte & Schneider, 2018).…”
Section: Introductionsupporting
confidence: 83%
“…Pincus and Kalman (2004) argue that irregularity in a price series changes perceived risk compared to regular, stylized series. Duxbury and Summers (2018) confirm these findings by showing that introducing irregularity to stylized series significantly increases perceived risk. As real-world price series usually display a high degree of irregularity, it adds value to stay close to realistic price paths to credibly identify the effect of price patterns on investor risk perception.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…falling prices and negative returns). Thus the adoption of momentum trading strategies when buying might be driven by a desire to reduce perceived risk or volatility (see Duxbury and Summers, 2017, for further discussion on how price sequences inform perceptions of risk and volatility, along with evidence that the two are not necessarily synonymous), with momentum buying perceived as lower risk than contrarian buying. Such an explanation, based on experimental findings in studies not confined to Chinese participants, would suggest the asymmetry of trading strategies across buy and sell decisions we report here need not be restricted to Chinese investors, but might hold more generally.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…168, no. 1108(May 2018 The number of bank branches per 100,000 adults in the EU fell by 28.7 per cent over the period [2009][2010][2011][2012][2013][2014][2015][2016]. Meanwhile, in excess of 1,700 branches closed in the US in the year to June 2017.…”
Section: C2 Retail Banking and Marketingmentioning
confidence: 99%